Comparative Studies Between Hydrophobic Catalysts Prepared for Isotopic Exchange Process - Preda, Anisoara; Stefanescu, Ioan; Brad, Sebastian; Vasut, Felicia; Pearsica, Claudia (Asian Journal of Chemistry, 2010)
The process for hydrogen isotopes separation is important for nuclear technology. Thus, the preoccupation is to find more efficient catalysts with a long operating time. The paper presents comparative studies between the physical and structural properties of hydrophobic catalysts. For the study of the isotope exchange water-hydrogen there were prepared the Pt/C/PTFE and Pt/SDB catalysts. These catalysts were manufactured by impregnation. For all the types of catalysts prepared there were determined the metal contain (active catalytically compound). The physical and texture properties such as specific surface, pore volume and its distribution after pore radius were also determined. The properties were determined by isotherm absorption to liquid nitrogen temperature 77.8 K through penetration with Hg. The specific surface was calculated according to BET equation; micro pore volume and its distribution after the range of radius were calculated using the approximation of cylindrical pore according to mathematical model Barret-Joyner-Haleda and nitrogen absorption data. One of the most important aspects for the utilization of hydrophobic catalyst in such processes is the stability radiation and impurities. Model catalysts are important because they offer a better prospect of controlling variables such as surface topography and composition. Using such a model catalysts it is better controlled the contamination of the surface structure.